IDENTIFYING THE INFLUENCE OF LOCAL COMMUNITY PARTICIPATION IN THE IMPLEMENTATION OF ECOTOURISM PRINCIPLES IN SANGHYANG KENIT TOURISM - Auliya Fathimah Az-zahra, Nurul
Tourism is one of the sectors in the service industry that has a significant influence on Indonesia's economic development. Therefore, tourism is a potentially lucrative sector to be developed. One example is the Sanghyang Kenit Tourism, which was officially inaugurated at the end of 2019 and holds potential for further development. However, the development potential in Sanghyang Kenit also poses threats in the form of negative externalities on the environment, local culture, and the local community. Consequently, a development concept is needed that focuses on minimizing these negative externalities. One applicable principle for Sanghyang Kenit is ecotourism, considering that the tourist destination primarily utilizes nature as its main attraction. The implementation of this principle should be supported by involving the participation of the local community, in line with Regional Regulation No. 4 of 2012 and in harmony with the efforts of the KBB Tourism and Culture Office to engage the community in the management of tourist destinations to collectively enhance the natural tourism potential of KBB. Thus, this research aims to determine the influence of local community participation in the development of Sanghyang Kenit tourism using the principles of ecotourism. Secondary data was gathered from institutions, print media, and electronic sources, while primary data was collected through observations and interviews. Data analysis was conducted using qualitative descriptive analysis, scoring analysis to identify ecotourism values in Sanghyang Kenit, and typology analysis of community participation to identify community types around Sanghyang Kenit. Based on the results of these identifications, an assessment was conducted to understand the influence of community participation values on the implementation of ecotourism in Sanghyang Kenit. The results of the ecotourism value identification using scoring analysis show that there are still deficiencies in the application of ecotourism principles in Sanghyang Kenit. The typology analysis of community participation indicates positive outcomes, as the community already possesses its own motivation and initiatives in developing Sanghyang Kenit tourism. This is reflected in a combined pattern of Induced Participation > Spontaneous Participation for certain indicators and Spontaneous Participation for others. In reviewing the influence of community participation values on the implementation of ecotourism in Sanghyang Kenit, it was found that, in general, the community participates in every ecotourism value. However, this participation is not uniform across all values, tending to prioritize the stability of tourism development. The results of this research are expected to serve as a reference for the government, community, and other stakeholders in the implementation of ecotourism values, especially in the case of the Sanghyang Kenit Tourism Destination.